The impact of the program of basketball, volleyball and handball on the situation-motorized capability of the first classes of the elementary school - E. Nikšić; E. Beganović; M. Joksimović (IP Iermakov S.S., 2020)
Purpose: Determining the state of the student and his situational-motor skills, and their comparison, enables the teacher to control his work in an immediate manner, and he programmes and implements well planned and additional contents in order to realize the set goals. In order to achieve these functions, it is necessary to determine the current state of the students, as well as the state after the implemented specific contents and programs. The aim of the research was to determine the partial changes (differences) of situational-motor abilities that were created under the influence of a four-month program of basketball, volleyball and handball in the pupils of the fifth grades of elementary school. Material: The study included N = 106 class V students, aged 10 to 11 years. The sample of respondents was divided into two subgroups, an experimental group (53 students), who conducted physical and health education classes according to the modified plan and program of sports games (basketball, volleyball and handball) for a half-year and control group (53 students) who attended regular classes from physical and health culture according to the current curriculum. 9 variables were used to assess situational-motor abilities. Descriptive statistics and discriminatory analysis were used to determine the changes (differences) in situational-motor skills. Results: The results of the research at the descriptive level showed certain differences between the groups in the final versus the initial measurements on the individual variables of situational motors. Based on the results of the discriminatory analysis, the relative contribution of each of the variables of the situational motor in the final measurement is seen. The SMKVLS (Running the ball with your hand in the slalom) and SMRBLZ (Throwing the ball against the wall for 30 seconds) variables are the biggest contributors, and the smallest SMOGCPM (Aiming the goal over the net from the basic stand) and SMOSD (Lower frontal serve). Conclusions: Physical and health culture in schools has the primary task of influencing positive transformation processes in all dimensions of students by applying appropriate content.